The Effectiveness of Marriage Guidance in Preventing Early Marriage: A Case Study at the Office of Religious Affairs (KUA) of Banyudono District - Sri Aristiyani; Syamsuddin Syamsuddin; Baehaqi Baehaqi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to analyze the implementation of marriage guidance at the Office of Religious Affairs (KUA) of Banyudono District, evaluate its effectiveness in preventing early marriage, and identify the factors contributing to child marriage. The research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, field observations, and documentation of marriage records and marriage dispensation data from 2020 to 2022. The research participants consisted of the Head of the KUA, religious counselors, administrative staff, and prospective brides and grooms who participated in premarital guidance programs. Data were analyzed using an interactive model, including data reduction, data display, and conclusion drawing. The findings indicate that the marriage guidance program has been implemented through premarital courses, community counseling, and educational programs for youth of marriageable age. The program has improved the knowledge and readiness of prospective couples; however, it has not been fully effective in reducing the rate of early marriage. The main contributing factors include premarital pregnancy, the perceived economic readiness of the male partner, and long-term relationships between couples. Therefore, strengthening marriage guidance programs through more comprehensive and collaborative approaches is necessary to enhance the effectiveness of early marriage prevention.